CTL MODEL TO ACTIVATE STUDENTS PARTICIPATION IN SPEAKING CLASS AT ENGLISH EDUCATION PROGRAM - Sukarni, Semi (VISION, 2014)
Abstract   In English Education Program Speaking Class starts at Semes- ter I until Semester V. It starts from imitative, intensive, responsive, interactive and extensive speaking.  In semester IV the students are expected to be able to communicate in local, national, or even inter- national settings about economic, social, environmental and politic issues.   However, speaking skill is not easily obtained. There are some factors that make speaking class is not maximal. It might be caused by class setting, teaching method, teaching materials,   students knowledge or even students interest. Further, getting speaking skills for all students in the classroom is not easy as they often face un- even participation, little talking time as certain students dominate the class. So, it is the lecturer s role to set the speaking activity that can facilitate both the active speakers and silence speakers. The si- lence speakers need to practice speaking in low-pressure situation such as in small group before practicing in high-pressure situation like presentation in class.   This research aims to describe the way to apply CTL model to activate  students  participation in  Speaking Class. Through CTL the lecturer relates the learning materials and students activities that are relevant to their needs in their real life. The reseacher choses issues on economy, social, and environment for the topic of  the discussion and she used prolem-solving approach.   The population of the research is the fourth semester of Eng-   lish Education Program in the academic year 2013/2014. The total number of population is 210 students which consists of 6 classes. The researcher took 65 students (30%)  from class A and B as the sample. The instrument used in the research were classroom obser- vation and  questionaire . The data were analyzed through descrip- tive analysis.   Based on the Dnding and the discussion, the conclusion can be drawn that CTL model is able to activate students  participation in Speaking Class of the fourth Semester of English Education Pro- gram in academic year of 2013/2014.     Key words: CTL, activate, participation, speaking